Fraud Detection Systems in Comparative Analysis in Indonesia and Australia - Emha Ichlasul Akbar; Lasih Amaliyah; Tina Amelia; Rozikin; Luki Setiawati (Greenation Research & Yayasan Global Resarch National, 2025)
This research aims to analyze fraud detection systems commonly implemented in Indonesia and Australia, identify differences in technological infrastructure, regulations, and human resource readiness, and describe case studies or concrete examples of fraud detection system implementation. Through the literature review method, this research collected 15 relevant scientific articles published between 2021 and 2024. The analysis shows that Australia has implemented a more sophisticated fraud detection system by utilizing technologies such as AI and data analytics, while Indonesia still relies on traditional methods with little technology adoption. Differences in technological infrastructure readiness, regulations, and HR training in both countries are important factors that affect the effectiveness of fraud detection systems. This research also provides recommendations to strengthen the internal control system in Indonesia by adopting modern technology, increasing HR capacity, and harmonizing regulations to create a more efficient and transparent system to prevent fraud.